Cost Benefit Analysis of Chaudhary Bakery Udhyog - Adhikari, Sarad (AJOIS: Academic Journal of Interdisciplinary Studies, 2024)
The research aims to explore the cost analysis and cost-benefit analysis with the help of Net Present Value and Internal Rate of Return in Chaudhary Bakery Udhyog (CBU). The research attempted to show the relationship between cost and benefit of the Chaudhary Bakery Udhyog. It followed descriptive cum analytical research design. The present research work covered a time period of five years 2017 to 2021. The presentation and analysis of benefit (net profit), benefit cost ratio (BCR), net present value (NPV) and internal rate of return (IRR).Benefit cost ratio (BCR) has been found greater than 1. Hence it can be concluded that this BCR greater than 1 may be due to the longer experience and good managerial ability. BCR is greater than 1 is represents the ratio of total benefits over total costs. It has been found that the bakery udhyog is running in profit. In the analysis NPV is greater than zero in every year. NPV is greater than zero is indicate that the total discounted value of benefit is greater than the total discounted value of costs. It is represent the udhyog performance is well. So, it is generating satisfactory profit in study period. The udhyog has a internal rate of return is 10.19%. It represents the discount rate at the NPV of Chaudhary Bakery Udhyog is equal to zero. It means present value of benefits equal to present value of costs of the udhyog. The IRR is greater than discount rate. It can be concluded that the udhyog is running well and performance is better.